(untitled) (Research, Society and Development, 2021)
The study aimed to make and validate an educational booklet on general nursing guidelines in the immediate preoperative period for students. This is a methodological study, with a quantitative and descriptive approach, which involves the investigation of methods for obtaining, organizing and analyzing data. To achieve the proposed objectives, three steps were taken: integrative literature review, assemble of the educational booklet and its validation by experts. Of the 11 invited experts, seven carried out the evaluation of the educational material and integrated this study. Most considered the educational booklet to be practical, with a logical sequence, easy to assimilate and suitable for the target audience. The content of general nursing guidelines in the immediate preoperative period proved to be mostly desirable and existing. It is believed that this proposal favors the use of active methodologies and expands the teaching possibilities in the field of nursing. It is suggested to carry out research that focuses on teaching methodologies aimed at the nurse in training. It is also emphasized the need for future studies to assess the effect of the educational booklet, presented here, on the acquisition of students’ knowledge; thus, it will be possible to certify its implications in the teaching-learning process.